Comparison of Five Benzodiazepine-Receptor Agonists on Buprenorphine-Induced µ-Opioid Receptor Regulation - Géraldine Poisnel; Martine Dhilly; Reynald Le Boisselier; Louisa Barre; Danièle Debruyne (Elsevier, 2009)
Abstract.: In this study, we compared the effects of five short-, medium-, or long-acting benzodiazepine-receptor agonists (BZDs) [alprazolam (APZ), clonazepam (CLZ), flunitrazepam (FLZ), loprazolam (LPZ), zolpidem (ZLP)], at two distinct doses, 0.2 and 2 mg/kg, on the cell surface regulation of μ-opioid receptor induced by 0.15 mg/kg buprenorphine (BPN) in specific regions of the rat brain. Using 0.312 - 5 nM [3H]-DAMGO concentrations and Scatchard plot analysis, Bmax (maximal receptor density) and Kd (dissociation constant) were determined at different brain regions of interest (amygdala, cortex, hippocampus, hypothalamus, thalamus). Acute BPN induced an expected down-regulation and addition of each of the BZDs to BPN induced less down-regulation than did BPN alone, sometimes while altering affinity. Some significant differences in the intensity of these effects were observed between BZDs. FLZ that is widely abused and enlarges BPN toxicity appeared the most potent to increase μ-cell surface receptor density at the lowest dose of 0.2 mg/kg. Besides, LPZ for which the effect on μ-opioid- receptor regulation appeared lower is considered to have a low risk of dependence in the epidemiological data banks. CLZ and ZLP (2 mg/kg) induced the strongest modification on μ-opioid-receptor density, but a substantial decrease in affinity could minimize the functional consequences. The reported changes were maximal in the amygdala, hippocampus, and thalamus. Among people using BPN and BZDs, the effects described here are likely to influence addictive behaviors and induce toxic effects that could be quantitatively different due to the quality of the BZD. Keywords:: benzodiazepine, buprenorphine, opioid receptor, interaction